HPV Vaccines: Types, Effectiveness and Safety-A Comprehensive Review - Swathi Ramesh, T C; Sanathan, Savitha R; Kiron, S S; Srikanth, M S (International Journal of Pharmaceutical Investigation, 2025)
The development of the HPV vaccine represents a groundbreaking achievement in the history of vaccine research. These vaccines, a pioneering category, effectively prevent infection by sexually transmitted microorganisms that affect mucous membranes. Importantly, they accomplish this without specifically triggering mucosal immunity, signifying a significant shift in preventive medicine. With an estimated efficacy of preventing 70% to 90% of HPV-associated cancers, these vaccines work by intercepting HPV infection before it enters the body, distinguishing them from traditional treatment-focused approaches. It is crucial to emphasize that the Virus-Like Particles (VLPs) used in all approved HPV vaccines are non-infectious and do not contribute to cancer development. The FDA initially recognized Gardasil in 2006, followed by Cervarix in 2008 and Gardasil 9 in 2014. Despite the availability of vaccines for a potentially deadly virus, immunization rates remain low. Factors contributing to this include limited knowledge about HPV among parents and adolescents, lack of awareness among healthcare providers, the cost of immunization and concerns about vaccine-related risks. National immunization programs are being implemented to promote vaccine usage among adolescent boys and girls, as the vaccine is recommended before age 26. Post-licensure studies have confirmed the safety and efficacy of the vaccine, which is consistent with pre-licensure findings.
Keywords: Adolescents; HPV vaccine; Human Papillomavirus; Immunization